Using induced pluripotent stem cells to explore genetic and epigenetic variation associated with Alzheimer's disease. (November 2017) - Imm, Jennifer; Kerrigan, Talitha L; Jeffries, Aaron; Lunnon, Katie
It is thought that both genetic and epigenetic variation play a role in Alzheimer's disease initiation and progression. With the advent of somatic cell reprogramming into induced pluripotent stem cells it is now possible to generate patient-derived cells that are able to more accurately model and recapitulate disease. Furthermore, by combining this with recent advances in (epi)genome editing technologies, it is possible to begin to examine the functional consequence of previously nominated genetic variants and infer epigenetic causality from recently identified epigenetic variants. In this review, we explore the role of genetic and epigenetic variation in Alzheimer's disease and how the functional relevance of nominated loci can be investigated using induced pluripotent stem cells and (epi)genome editing techniques.